2020
DOI: 10.47067/reads.v6i2.222
|View full text |Cite
|
Sign up to set email alerts
|

Does Trade Openness Transfer Pollution across Borders: An Experience of Pakistan

Abstract: The study aims to empirically explore the link between trade openness and emission level in Pakistan by using Johansson co integration technique during the period from1972 to 2019. The empirical strategy of the study progressively incorporates models from zero interaction terms to complete interaction terms for analyzing the relationship between trade openness and emission level in the presence of scale, composition and technique effect. The variable of the trade openness appeared in all the models with negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Under this relief package, the government increased 50% of the Benazir Income Support Programme (BISP) to enhance the quality of life of the lower-income groups. Besides, 5.2 million beneficiaries through the BISP's ongoing National Socio-Economic Registry (NSER) and officials included more people in the package (40).…”
Section: Economic Relief Package For Improving Quality Of Lifementioning
confidence: 99%
“…Under this relief package, the government increased 50% of the Benazir Income Support Programme (BISP) to enhance the quality of life of the lower-income groups. Besides, 5.2 million beneficiaries through the BISP's ongoing National Socio-Economic Registry (NSER) and officials included more people in the package (40).…”
Section: Economic Relief Package For Improving Quality Of Lifementioning
confidence: 99%
“…Gülşen and Özmen (2020) considered that emerging markets are much more sensitive to global financial cycles under managed than floating exchange rate regimes. Batool et al (2020) suggested that the COVID-19 pandemic has disrupted the economies all around the world, meaning that the economic fallout from preventive measures such as lockdowns is enormous. Asghar et al (2020) argued that this is the worst economic downturn since the Great Depression of the 1930s.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Batool et al (2020) suggested that the COVID-19 pandemic has disrupted the economies all around the world, meaning that the economic fallout from preventive measures such as lockdowns is enormous. Asghar et al (2020) argued that this is the worst economic downturn since the Great Depression of the 1930s. COVID-19 represents a new type of coronavirus that transfers extremely fast from human to human and started spreading in late December 2019 in Wuhan, China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic has overwhelmed the health sector beyond the normal functioning to sensitive caretaking. This progressing widespread appeared to bring devastating effects on global economies, with Pakistan facing substantial setbacks [ 7 ]. In particular, the mental toll of COVID-19 challenged the frontline workers to deal with high-stress situations such as long working hours, thus influencing normal healthcare functioning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%